Phytoliths as a tool for investigations of agricultural origins and dispersals around the world. (April 2016) - Ball, Terry; Chandler-Ezell, Karol; Dickau, Ruth; Duncan, Neil; Hart, Thomas C.; Iriarte, Jose; Lentfer, Carol; Logan, Amanda; Lu, Houyuan; Madella, Marco; Pearsall, Deborah M.; Piperno, Dolores R.; et al.
Abstract: Agricultural origins and dispersals are subjects of fundamental importance to archaeology as well as many other scholarly disciplines. These investigations are world-wide in scope and require significant amounts of paleobotanical data attesting to the exploitation of wild progenitors of crop plants and subsequent domestication and spread. Accordingly, for the past few decades the development of methods for identifying the remains of wild and domesticated plant species has been a focus of paleo-ethnobotany. Phytolith analysis has increasingly taken its place as an important independent contributor of data in all areas of the globe, and the volume of literature on the subject is now both very substantial and disseminated in a range of international journals. In this paper, experts who have carried out the hands-on work review the utility and importance of phytolith analysis in documenting the domestication and dispersals of crop plants around the world. It will serve as an important resource both to paleo-ethnobotanists and other scholars interested in the development and spread of agriculture. Highlights: The utility of phytoliths for investigating the origins of agriculture is reviewed by experts around the world. Numerous morphological and size criteria differentiate crop plants and inform diverse questions on prehistoric agriculture. Phytoliths have and will continue to be of significant, often unique, importance for this fundamental topic.